RADIOGRAPHIC IMAGE QUALITY ANALYSIS IN THORAX, ABDOMEN, AND BONE FRACTURE EXAMINATIONS WITH KV AND MAS PARAMETER VARIATIONS - Zahra Putri Rahman; Rhamdani Syahputra; Nani Lasiyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This experimental study at Petala Bumi Public Hospital (Jan–Apr 2025) aimed to determine the optimal tube voltage (kV) and tube current–time product (mAs) settings to enhance conventional X-ray image quality for thoracic, abdominal, and bone fracture examinations. Radiographs were taken using varied kV–mAs combinations and analyzed with ImageJ software through grey-level histograms to assess brightness (mean pixel intensity) and contrast (standard deviation). The thoracic image with a mean of 127.117 and SD of 83.331 showed the best balance of brightness and contrast. The optimal abdominal image had a mean of 107.703 and SD of 66.725, while the best bone fracture image had an SD of 65.463, ensuring clear fracture visibility. The study confirms the effectiveness of ImageJ in objective image-quality evaluation and highlights the importance of adjusting exposure parameters to improve diagnostic clarity without increasing radiation dose.